PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN KAS, DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PERUSAHAAN PENYEDIA SPARE PART OTOMOTIF PERIODE 2007-2011 - Yuliyati Yuliyati; Sunarto Sunarto (Jurnal Akuntansi, 2014)
This research aimed to determine the effect of working capital turnover, cash turnover, and capital structure partially or simultaneously on the profitability of the companies of automotive spare parts 2007-2011. Profitability was measured by using return on investment (ROI).The data used was secondary data from the financial statements of the sample companies. Data analysis method used was the classic assumption of hypothesis testing. The statistical method used was multiple linear regression analysis. The sampling method used was purposive sampling. The dependent variable in this research was the profitability (Y), the independent variables consisted of working capital turnover (X1), cash turnover (X2), and capital structure (X3).The results showed that the partial of working capital turnover has no any effect on return on investment (ROI), cash turnover affected the return on investment (ROI), capital structure affected the return on investment (ROI). Simultaneously, working capital turnover, cash turnover, and capital structure affected towards the return on investment (ROI) on the companies of automotive spare parts 2007-2011. Keywords : working capital turnover, cash turnover, structure capital, and return on investment (ROI)